2019
DOI: 10.2147/ptt.s186637
|View full text |Cite
|
Sign up to set email alerts
|

<p>A narrative review of psoriasis and multiple sclerosis: links and risks</p>

Abstract: The association of psoriasis (PsO) with other autoimmune and autoinflammatory diseases has long been a topic of interest. Although previous studies have attempted to clarify the specific relationship between PsO and multiple sclerosis (MS), it remains obscure, with limited and conflicting evidence regarding a link between the two entities. Herein, we review the etiology, pathogenesis, and treatment of each disease and present the available literature to-date regarding a possible relationship between PsO and MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 85 publications
(112 reference statements)
1
32
0
Order By: Relevance
“…Psoriasis is an autoimmune inflammatory disorder that may affect the skin, associating epidermal proliferation, due to a dysregulation of the immune system; pro-inflammatory cytokines, including IL-12 and -23 and TNF-α, are produced, and the inflammatory milieu is developed and maintained with contribution from various cells, such as T-helper cells 1 and 17, keratinocytes, and dendritic cells alongside various immune cells [119][120][121][122].…”
Section: Psoriasismentioning
confidence: 99%
“…Psoriasis is an autoimmune inflammatory disorder that may affect the skin, associating epidermal proliferation, due to a dysregulation of the immune system; pro-inflammatory cytokines, including IL-12 and -23 and TNF-α, are produced, and the inflammatory milieu is developed and maintained with contribution from various cells, such as T-helper cells 1 and 17, keratinocytes, and dendritic cells alongside various immune cells [119][120][121][122].…”
Section: Psoriasismentioning
confidence: 99%
“…While some small studies and case reports have suggested an increased risk, larger studies were unable to confirm this finding. 7 The role of TNF in demyelinating disorders is yet incompletely understood, and several cases developing multiple sclerosis and Guillain-Barr e in patients receiving TNF-blockers have been reported. 7 As psoriasis requires a long-term treatment, patients with a history of malignancy or developing cancer during systemic psoriasis treatment are a relatively frequent event.…”
Section: Introductionmentioning
confidence: 99%
“…7 The role of TNF in demyelinating disorders is yet incompletely understood, and several cases developing multiple sclerosis and Guillain-Barr e in patients receiving TNF-blockers have been reported. 7 As psoriasis requires a long-term treatment, patients with a history of malignancy or developing cancer during systemic psoriasis treatment are a relatively frequent event. Psoriasis patients carry an increased risk for different types of cancer and cancer mortality especially from liver, oesophageal and pancreatic cancer and lymphoma.…”
Section: Introductionmentioning
confidence: 99%
“…Psoriasis is a chronic, immune-mediated, inflammatory disorder with an estimated prevalence of approximately 2% to 4% in Europe. 1 Moderate to severe psoriasis is frequently associated to several comorbidities, such as abdominal obesity, hypertension, diabetes mellitus, dyslipidemia, cardiovascular disorder, and chronic kidney disease. 2 Multiple sclerosis is the most common immune-mediated demyelinating disease of the central nervous system (CNS) affecting young adults with a strong female prevalence.…”
Section: Introductionmentioning
confidence: 99%
“…2 Multiple sclerosis is the most common immune-mediated demyelinating disease of the central nervous system (CNS) affecting young adults with a strong female prevalence. 1 Psoriasis and multiple sclerosis present similarities in genetic risk factors and immune system dysregulation. 1 The association between these two conditions has been suggested but, to date, it is not clearly elucidated since results of multiple studies are conflicting.…”
Section: Introductionmentioning
confidence: 99%